Korelasi Signifikan antara Kecepatan Superfisial dan Viskositas Cairan Menggunakan Pola Aliran Dua Fase pada Pipa Mini dengan Kemiringan 30 Derajat - Sukamta, Sukamta; Sudarja, Sudarja (TURBO [Tulisan Riset Berbasis Online], 2019)
This paper present a novel result of significant correlation between superficial velocity and viscosity on two-phase flow pattern in mini channel with slope of 30o against horizontal.             This research used glass mini pipe 1.6 mm diameter and 130 mm length with a slope of 30 ° to the horizontal position. The working fluid used is air - water with glycerin of 40%, 50%, 60%, 70% concentration. Liquid superficial velocity JL = 0.033 - 4.935 m / s and gas superficial velocity JG = 0.025 - 66.3 m / s. High-speed Camera was used to visualize the flow pattern.Summing up the result, it can be concluded that gas/water superficial velocity and viscosity of liquid effected significantly to form a flow patterns. In this paper, flow pattern of plug, bubbly, slug annular, annular, and churn were successfully found. Flow pattern maps showed that the distribution of different flow patterns due to the increased viscosity. Comparing with previous studies showed that there is a good agreement result.Keywords: high-speed, superficial velocity, viscosity, flow pattern.